2010
DOI: 10.1111/j.1365-2214.2010.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of children with ADHD in a natural and built setting

Abstract: These results suggest that natural areas provide a consistent positive environment for children with ADHD. However, more research is needed to obtain a fuller understanding of the influences of the physical environment on children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 35 publications
3
57
1
3
Order By: Relevance
“…Furthermore, perceived restorativeness (H4) was higher after the natural environment condition (vs. built). Findings from previous studies are in line with our results, both for attention (Wells, 2000; Faber-Taylor and Kuo, 2009, 2011) and perceived restorativeness (Wells, 2000; Bagot, 2004; van den Berg and van den Berg, 2011; Chawla et al, 2014; Bagot et al, 2015; Berto et al, 2015). However, no effects were found on impulse control irrespective of the environmental setting (Schutte et al, 2015), disconfirming H3.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, perceived restorativeness (H4) was higher after the natural environment condition (vs. built). Findings from previous studies are in line with our results, both for attention (Wells, 2000; Faber-Taylor and Kuo, 2009, 2011) and perceived restorativeness (Wells, 2000; Bagot, 2004; van den Berg and van den Berg, 2011; Chawla et al, 2014; Bagot et al, 2015; Berto et al, 2015). However, no effects were found on impulse control irrespective of the environmental setting (Schutte et al, 2015), disconfirming H3.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the natural environment condition, results are in line with the findings from Study 1 but also from other studies (Wells, 2000; Faber-Taylor et al, 2001; Bagot, 2004; van den Berg and van den Berg, 2011; Corraliza et al, 2012; Bagot et al, 2015; Berto et al, 2015). Furthermore, the present research showed the positive effect of nature on psychological restoration: (a) in a field study, providing both a crossover and a between-subject design; (b) in a real life situation (our study was embedded in school activities); (c) using preexistent standardized tools for measuring attention involved in school time activities; (d) comparing two different outdoor environments; (e) testing attention restoration in the morning and in the afternoon; (f) assessing attention restoration that occurred after recess time spent in a team play activity and with free play.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of contact with nature (Louv, 2008) has been suggested to be one of the primary reasons underlying the recent surge in childhood maladies like Attention Deficit Hyperactivity Disorder (ADHD) (van der Berg and van der Berg, 2010). Over 6 million children in the United States are struggling to cope with chronic attentional deficit or attention-deficit/hyperactivity disorder (ADHD) (CDC, 2017a).…”
Section: Physical and Mental Health Disordersmentioning
confidence: 99%
“…19 Greenspace has the ability to improve overall wellbeing, decrease stress levels, and reduce symptoms of depression, anxiety, and attention-deficit/hyperactivity disorder. 2024 However, no previous studies have examined whether greenspace could reduce aggressive behaviors in urban-dwelling adolescents.…”
Section: Introductionmentioning
confidence: 99%